Segurança de uso e efeito clínico da aplicação intra-articular de toxina botulínica tipo a para dor articular em equinos - Beck Júnior, Antônio Alcemar (2022)
The complex synovitis-osteoarthritis is the main cause of lameness in horses, directly impacting their quality of life. Botulinum toxin type A has been explored in human and canine medicine as a very promising option for patients suffering from chronic joint pain. The first study aimed to investigate whether a single injection of botulinum toxin type A (BoNT-A) would produce adverse effects on physical parameters, on lameness evaluation and potential synovial fluid inflammatory response. One randomly selected radiocarpal joint was treated with 50 U of BoNT-A in eight horses, and the contralateral joint received saline solution. All horses received injections at day 0 and were re-evaluated twice daily for seven days for heart rate (HR), respiratory rate (RR), rectal temperature (RT), mucous membrane color, capillary refill time, intestinal motility, appetite, water intake, defecation, urination, and attitude. At these same time points, joint pain and circumference were assessed. Objective lameness evaluations were performed once daily for seven days and synovial fluid samples were collected at baseline, post-injection hour (PIH) 24 and PIH 168 and evaluated for synovial fluid parameters. HR and RT remained clinically unaltered, despite oscillations over time (p=0.001). The remaining clinical parameters were unaltered by treatment or time (p>0.05). Joint pain was not elicited by flexion and palpation in both limbs as well as carpal circumference was unaltered (p=0.88). Lameness was observed only on saline injected limbs. Cellular parameters evaluated in synovial fluid samples from both carpi had significantly increased from baseline to PIH 24, decreasing at PIH 168. In conclusion, intra-articular (IA) injection of 50 U of BoNT-A is suggested to be a safe therapy for IA use in horses. In the second study, the objective was to evaluate the clinical effect of intra-articular (IA) injection of BoNT-A in horses with chronic distal tarsal osteoarthritis. Nine horses were selected for the study after a complete physical and radiographic assessment. Horses also underwent an objective lameness examination and were included if they had a hind limb impact lameness (Pmin variable ≥ 3mm), which positively responded (≥50%) to the tarsometatarsal (TMT) and centrodistal (CD) joints anesthetic block. Presence of radiographic signs of osteoarthritis also was an inclusion criterion. After, horses randomly received IA injection with 50 U of BoNT-A or equivalent volume of saline solution. Five horses were included in the BoNT-A group, whereas four individuals were allocated in the placebo group. The horses were re-evaluated at post-injection days (PID) 1, 7, 15, 30, 60, 90, 120, 150 and 180. Success criteria included: decrease of Pmin values (≤ 3mm) and abolishment of lameness on the baseline lame limb with lameness shifting to the contralateral limb, in cases of individuals bilaterally affected by the condition. Additionally, a percentage of lameness improvement was calculated for all horses at all timepoints. Significant improvement was observed in horses from TBA group when compared with placebo at PID 90 (p<0.05), 120 (p<0.001), 150 (p<0.001) and 180 (p<0.05). Individually, 40% (2/5) of horses from the TBA group had a complete improvement (100%) in lameness at all the timepoints. In the same group, 80% (4/5) of horses demonstrated complete improvement for at least four timepoints evaluated. Only one horse from this group did not present complete improvement during the study, with mean ± s.e. 51.53±19.36%. Higher percentages of lameness improvement were observed at the PID 60 (95.92±9.13%). In contrast, no horses from the placebo group demonstrated complete lameness improvement after treatment. Results of this study suggested that the IA injection with 50 U of BoNT-A was effective in reducing lameness in horses with chronic distal tarsal osteoarthritis, mainly after 90 days post-injection.